2013
DOI: 10.1093/carcin/bgt280
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inhibition of urinary bladder cancer growth and muscle invasion by allyl isothiocyanate and celecoxib in combination

Abstract: Allyl isothiocyanate (AITC) occurs in cruciferous vegetables that are commonly consumed by humans and has been shown to inhibit urinary bladder cancer growth and progression in previous preclinical studies. However, AITC does not significantly modulate cyclooxygenase-2 (Cox-2), whose oncogenic activity has been well documented in bladder cancer and other cancers. Celecoxib is a selective Cox-2 inhibitor and has been widely used for treatment of several diseases. Celecoxib has also been evaluated in bladder can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Selective inhibitors of COX-2, such as etoricoxib and celecoxib, can slow cell growth and induce apoptosis in tumor cell lines, such as BC, in both humans and animal models [ 8 , 21 - 23 ]. It has been shown that prolonged treatment with selective COX-2 inhibitors is directly related, unlike aspirin, to a significant increase in cardiovascular risk, thereby excluding the possible preventive use of these drugs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective inhibitors of COX-2, such as etoricoxib and celecoxib, can slow cell growth and induce apoptosis in tumor cell lines, such as BC, in both humans and animal models [ 8 , 21 - 23 ]. It has been shown that prolonged treatment with selective COX-2 inhibitors is directly related, unlike aspirin, to a significant increase in cardiovascular risk, thereby excluding the possible preventive use of these drugs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main target in determining the chemopreventive effect of aspirin and other non-steroidal anti-Inflammatory drugs (NSAIDs) is the inhibition of cyclooxygenase (COX) or prostaglandin-endoperoxide synthase, especially its isoform 2, which is overexpressed in many tumor cell lines, including bladder cancer (BC) [ 2 - 7 ]. Many studies have shown that COX inhibitors have a preventive effect and are able to induce remission of BC in animal models [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Celecoxib, a selective COX-2 inhibitor, is used for various pathological conditions worldwide. Thus, to clarify the anti-cancer effects of a combination of celecoxib and AITC, in vitro studies employing AY-27 bladder cancer cells and in vivo studies with the F344/AY-27 rat bladder urothelial cell carcinoma model were performed [61]. In vitro, AITC first showed no significant impact on COX-2 expression, and PGE2 production was confirmed.…”
Section: Combination Therapy Of Allyl Isothiocyanate and Conventionalmentioning
confidence: 99%
“…Interest in allyl isothiocyanate arises from the fact that it is reported to exhibit numerous health-promoting beneficial effects. These include (a) antifungal activities in bread [4] and on corn kernels and corn flour [5] ; (b) antimicrobial effects against multiple foodborne pathogens and spoilage bacteria in laboratory media, water, and on/in food [4] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ; (c) nematicidal effects against Meloidogyne incognita [22] ; (d) inhibition of mycotoxin toxicity [23] ; (e) insecticidal activity against scarab beetle larvae (Coleoptera: Scarabedaes), contaminants of ornamental crops [24] ; (f) trypanocidal activity against Trypanosoma brucei parasites [25] ; and (g) anticancer, cardioprotective, neuroprotective, antidiabetic, and other beneficial properties [26] , [27] , [28] , [29] . It is also relevant to note that SH-containing amino acids and peptides such as cysteine and glutathione that are present in meat and in vivo interfered with the antimicrobial activity allyl isothiocyanate against Escherichia coil O157:H7, presumably by forming inactive adducts [30] , [31] .…”
Section: Introductionmentioning
confidence: 99%